Pengaruh Intensitas Penggunaan Media Sosial dan Manajemen Waktu terhadap Prokrastinasi Akademik Siswa Kelas XI SMA Negeri 1 Muaro Jambi: Penelitian - Pola Tiurmawati Turnip; Refnida; Destri Yaldi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine the effect of intensity of social media use and time management on academic procrastination of class XI students of public high school 1 muaro jambi both partially and simultaneously. This research is a quantitative approach with ex-post facto method. The population in this study were 11th grade students of public high school 1 muaro jambi with a sample of 123 respondents and taken by simple random sampling. The data analysis technique used is descriptive statistical analysis. The results showed that partially the variable Intensity of Social Media Use had a positive and significant effect on academic procrastination with a tcount > ttable value. Partially, the Time Management variable on academic procrastination has a negative and significant effect with a tcount > ttable value. Simultaneously, the intensity of social media use and time management has a positive and significant effect on academic procrastination.